(untitled) (Ius Novum, 2024)
The article is of a scientific and research nature and its subject is the subject matter of the crime of bribery of a creditor (Article 302 § 2 of the Penal Code). The aim of the article is to clarify the doubts it raises. It relates the historical antecedents of this crime in Polish Criminal Law and analyses the notions used in this article such as: creditor, economic benefit, forms of offering this benefit, promise of benefit, acting in prejudice of creditors, relation between acts of creditor and bankruptcy proceedings or proceedings tending to avoid bankruptcy, bankruptcy proceedings, other proceedings which avoid bankruptcy. The article proposes the interpretation of all this notions based on doctrine’s opinions and jurisprudence.